PRINSIP E-STRATEGY YANLIK SMART DALAM PELAYANAN PUBLIK DI KABUPATEN PURWAKARTA - Nuraeni, Hikmah; Noor Azijah, Dewi; Debby Mahendra Putri, Lolita (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Yanlik Smart is a website that focuses on public services through public satisfaction surveys to improve public services in Purwakarta Regency. Therefore, Yanlik Smart is here to help monitor the extent of public services provided by Regional Apparatus Organizations (OPD) through public satisfaction surveys. The features in Yanlik Smart are home, OPD, achievements, monitoring and evaluation, and login. Challenges in implementing Yanlik Smart include admin changes in OPDs, server downtime, and service recipients who do not understand the Yanlik Smart filling process, as well as some people who do not have smartphones to fill out surveys digitally. The purpose of this study is to analyze the urgency of Yanlik Smart in public services in Purwakarta Regency, so this study focuses on whether Yanlik Smart is appropriate or not as a tool in improving public services in Purwakarta Regency. The research method is a qualitative method with a case study design. The results of this study indicate that Yanlik Smart is aligned with the regional development vision, has a clear institutional structure, and is supported by information technology-based strategies and policies. Although specific regulations regarding this system are not yet available, its implementation remains guided by broader regulations. In addition, regular monitoring and evaluation are required because human resource readiness is an important factor in the success of Yanlik Smart implementation.